Chitosan-functionalized Ag nanoparticles for degradation of methylene blue: effect of chitosan pre-treatment - Setiabudi, H. D.; Rohayu, Jusoh; N. S., Kamarudin; N. F. , Sukor (Globeedu Group, 2017)

(untitled)
Coloured wastewater discharge mainly from textile industries will affect the water source and became pollution. Methylene blue is one of common dyes exist in every textile industries. Silver is known as a photocatalyst for the removal of environmental contaminants. Due to high tendency to agglomeration happened, biomaterial was used to support the metal which is chitosan. In this research, chitosan will be treated with different condition by using different type of chemical followed by preparation of AgO/Chitosan. From FTIR study, found that existence of AgO bound with chitosan. Photocatalytic process of methylene blue clearly inllutrates that NaOH treated chitosan was very active for the photo degradation of methylene blue.